Underutilization of Death Row Clemency and Its Implications for Justice and Human Rights - Hatarto Pakpahan; Fathor Rahman (Faculty of Law Universitas Jenderal Soedirman, 2025)
The death penalty in Indonesia is controversial because it is contrary to human rights principles, although executions are carried out based on the sovereignty of national law. The uncertainty of the clemency process has a double impact: the convict experiences an unclear fate, and the state is criticized for the inconsistent application of the law. The